Combination of inflammatory and vascular markers in the febrile phase of dengue is associated with more severe outcomes - Vuong, Nguyen Lam; Lam, Phung Khanh; Ming, Damien Keng Yen; Duyen, Huynh Thi Le; Nguyen, Nguyet Minh; Tam, Dong Thi Hoai; Duong Thi Hue, Kien; Chau, Nguyen VV; Chanpheaktra, Ngoun; Lum, Lucy Chai See; Pleités, Ernesto; Simmons, Cameron P; et al. (eLife, 2021)
Background:. Early identification of severe dengue patients is important regarding patient management and resource allocation. We investigated the association of 10 biomarkers (VCAM-1, SDC-1, Ang-2, IL-8, IP-10, IL-1RA, sCD163, sTREM-1, ferritin, CRP) with the development of severe/moderate dengue (S/MD). Methods:. We performed a nested case-control study from a multi-country study. A total of 281 S/MD and 556 uncomplicated dengue cases were included. Results:. On days 1-3 from symptom onset, higher levels of any biomarker increased the risk of developing S/MD. When assessing together, SDC-1 and IL-1RA were stable, while IP-10 changed the association from positive to negative; others showed weaker associations. The best combinations associated with S/MD comprised IL-1RA, Ang-2, IL-8, ferritin, IP-10, and SDC-1 for children, and SDC-1, IL-8, ferritin, sTREM-1, IL-1RA, IP-10, and sCD163 for adults. Conclusions:. Our findings assist the development of biomarker panels for clinical use and could improve triage and risk prediction in dengue patients. Funding:. This study was supported by the EU's Seventh Framework Programme (FP7-281803 IDAMS), the WHO, and the Bill and Melinda Gates Foundation.
Gesehen am 18.10.2021